Late Preterm Infants' Social Competence, Motor Development, and Cognition - You, Jia; Yang, Hong-juan; Hao, Mei-chen; Zheng, Jing-jing (Frontiers in Psychiatry, 2019)
The aim of this study was to compare the social competence, motor development, and cognition of late preterm infants (LPIs) with full-term infants. Several studies in the recent past indicated that LPIs are at high risk of social development problems. We compared the development of motor skills, cognition, and social competency of LPIs with full-term infants at between 2 and 2.5 years old. The Chinese versions of the Gesell Development Diagnosis scale and the Normal Development of Social Skills from Infants to Junior High School Children scale were used for the assessment. LPIs were not more socially competent than their full-term counterparts. Each skill—namely, adaptability, gross motor, fine motor, language, and personal-social responses—was separately associated with the total level of social skills. It was found that gross motor skills had a positive correlation with the self-help and locomotive abilities, and fine motor skills had a positive association with locomotion abilities. LPIs had risk factors due to their delayed social skills in areas including motor disorders and physiological and perinatal factors. LPIs under three were at a higher risk of impairment in social competency. Therefore, it is recommended that they be monitored regularly to identify the development of social and cognitive disorders at an early stage.